Cancer Predisposition Syndromes and Medulloblastoma in the Molecular Era - Carta, Roberto; Del Baldo, Giada; Miele, Evelina; Po, Agnese; Besharat, Zein Mersini; Nazio, Francesca; Colafati, Giovanna Stefania; Piccirilli, Eleonora; Agolini, Emanuele; Rinelli, Martina; Lodi, Mariachiara; Cacchione, Antonella; et al. (Frontiers in Oncology, 2020)
Medulloblastoma is the most common malignant brain tumor in children. In addition to sporadic cases, medulloblastoma may occur in association with cancer predisposition syndromes. This review aims to provide a complete description of inherited cancer syndromes associated with medulloblastoma. We examine their epidemiological, clinical, genetic, diagnostic features and therapeutic approaches, including their correlation with medulloblastoma. Furthermore, according to the most recent molecular advances, we describe the association between the various molecular subgroups of medulloblastoma and each cancer predisposition syndrome. Knowledge of the aforementioned conditions can guide pediatric oncologists in performing adequate cancer surveillance. This will allow clinicians to promptly diagnose and treat medulloblastoma in syndromic children, forming a team with all specialists necessary for the correct management of the other various manifestations/symptoms related to the inherited cancer syndromes.